Konsep dan Perkembangan Pemikiran Tentang Tanggung Jawab Sosial Perusahaan - Erman Rajagukguk (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The legal framework pertinent to Indonesian companies has assigned the companies to accomplish  what so called by Corporate Social Responsibility (CSR). While  in its wider concept  CSR encompasses  human rights, labor, consumers protection and environment, in its simpler concept, it is translated as the welfare development of the concerned surrounding community.